Leucine dose-response on muscle maintenance and fat loss in young men with BMI 23 and above after 4 weeks of alternate-day fasting - Na, Brandon Qi En (Nanyang Technological University, 2020)
Background: To reduce the health risks that comes along with obesity and being overweight, individuals are often required to lose weight. However, weight loss often reduces LM, leading to health, functional and psychological issues. Purpose and Aims: Determine whether different dosages of leucine have different effects on preservation on LM and loss of FM, FM%, WHR and BW. Also, determine effect of 4 weeks of ADF on pre-post LM, FM, FM%, WHR and BW. Hypotheses: Different dosages of leucine will have different effects on LM, FM and BW. There will be a significant decrease between pre-post intervention FM, FM%, WHR and BW, but no significant decrease in LM. Methods: 22 young males with BMI ≥ 23 in a randomized, controlled double blind study design underwent 4 weeks of ADF and only consumed food provided by the study. LM, FM, FM % were measured using a DXA scan, BW and WHR were measured using a stadiometer and measuring tape, respectively. Results: No significant differences were observed between different leucine dosages groups for LM, FM, FM%, WHR and BW. However, there was a significant decrease between pre-post intervention LM, FM, FM%, WHR and BW, with a mean decrease of (918g), (2242g), (1.9%), (0.018) and 3.27kg respectively. Conclusion: Different leucine dosages does not have different effects on LM, FM, FM%, WHR and BW. 4 weeks of ADF is a viable option for overweight and obese individuals to lose FM, FM%, WHR and BW to reduce its associated health risks.